2004
DOI: 10.1021/bi049162o
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Quinone Reductase 2 in Complex with Resveratrol,

Abstract: Resveratrol has been shown to have chemopreventive, cardioprotective, and antiaging properties. Here, we report that resveratrol is a potent inhibitor of quinone reductase 2 (QR2) activity in vitro with a dissociation constant of 35 nM and show that it specifically binds to the deep active-site cleft of QR2 using high-resolution structural analysis. All three resveratrol hydroxyl groups form hydrogen bonds with amino acids from QR2, anchoring a flat resveratrol molecule in parallel with the isoalloxazine ring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
230
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(245 citation statements)
references
References 64 publications
10
230
2
3
Order By: Relevance
“…This recently identified pathway involves inhibition of the ubiquitin-independent degradation of p53 in 20S proteasomes through its binding to NQO1 or NQO2 (20,24,25). We found that dicoumarol, which is known to interfere with the NQO1 binding to p53, and resveratrol, a highly specific inhibitor of NQO2 (31), can mitigate the stabilization of p53 and the induction of p53-dependent reporter in response to treatment with myxothiazol or PALA. Similar to the drug inhibitors, the p53-inducing effect of myxothiazol was alleviated in the cells with NQO1 or NQO2 downregulated by specific shRNAs.…”
Section: Discussionmentioning
confidence: 68%
“…This recently identified pathway involves inhibition of the ubiquitin-independent degradation of p53 in 20S proteasomes through its binding to NQO1 or NQO2 (20,24,25). We found that dicoumarol, which is known to interfere with the NQO1 binding to p53, and resveratrol, a highly specific inhibitor of NQO2 (31), can mitigate the stabilization of p53 and the induction of p53-dependent reporter in response to treatment with myxothiazol or PALA. Similar to the drug inhibitors, the p53-inducing effect of myxothiazol was alleviated in the cells with NQO1 or NQO2 downregulated by specific shRNAs.…”
Section: Discussionmentioning
confidence: 68%
“…However, 50 μM resveratrol promoted fat mobilization in white adipocytes by repressing PPARγ in 3T3-L1 cells, 93) which is inconsistent with our finding that 5 μM resveratrol activates PPARα, β/δ, and γ in BAECs. 12,32) Other candidate targets of resveratrol such as quinone reductase 2 (QR2), 94) AMP-activated protein kinase (AMPK), 95) and PPARγ coactivator (PGC)-1α 96) have also been reported. Resveratrol inhibits purified QR2, with a dissociation constant of 35 nM 94) ; 10 μM resveratrol as well as apigenin stimulated AMPK in HepG2 hepatoma cells 95) ; and 50 μM resveratrol induced PGC-1α-responsive genes such as medium chain acylCoA dehydrogenase, cytochrome C, and estrogen receptorrelated receptor α in C2C12 cells infected with an adenovirus expressing PGC-1α.…”
Section: Link To Sirt1 and Other Targetsmentioning
confidence: 99%
“…Resveratrol further inhibits cyclooxygenases [19], and could therefore act through some of the same mechanisms as aspirin. An unbiased approach to select resveratrol-binding proteins revealed quinone reductase 2, which is inhibited by resveratrol, as one of the highest affinity targets, although the significance of this observation is not yet known [20]. Fully defining the targets of resveratrol that are biologically relevant is an enormous task, made more difficult by questions of whether effects are either direct or indirect, and often conflicting results in different systems.…”
Section: Introductionmentioning
confidence: 99%